Aplikasi Model Adative Neuro Fuzzy Inference System Untuk Peramalan Pasang Surut Di Air Laut (Studi Kasus Pelabuhan Tanjung Buton Siak) - Sari, Fitria; Hendri, Andy; Suprayogi, Imam (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Previous researchers have much success using the model Adaptive Neuro Fuzzy Inference System (ANFIS) as a forecasting model for hydrological analysis. Reliability of ANFIS models need to be tested, especially to farecast of the tidal. In this research, ANFIS models which built using data tidal observations in Tanjung Buton (2004). The result of tidal forecasting by using ANFIS models show excellent results with value the test statistic parameters of the correlation coefficient (R) more than 0.87 that is in category of very strong correlation, statistic parameters of RMSE (root mean square error) 0.445 m, and the test parameters of the average valuation relative error by 11,8%. In comparison the tidal forcasting results used ANFIS models with tidal forcasting results used the Admiralty method, values of the parameter test by mean relative error used ANFIS model is smaller with value of 11.8%, while values of the parameter test by mean relative error used Admiralty method is larger that is 22.4%. Keywords: hydrological analysis, tidal forecasting, softcomputing, ANFIS.